Teaching cases in tourism, hospitality and events - Dixit, Saurabh Kumar; Piramanayagam, Senthilkumaran (Wallingford, Oxfordshire CAB International, 2023)
"The tourism, hospitality and events industries comprise one of the largest and most diverse workforces in the world, creating high demand for graduates with strong technical and managerial competencies. Case-based learning encourages students to think, understand, and apply the concepts and theories they're taught into practical, everyday situations faced in the world of work. Providing a broad selection of extensive global cases, this book forms a comprehensive one-stop-shop resource for readers to test their analytical skill and abilities in solving complex management issues. Cases include teaching notes to reflect theoretical perspectives, as well as questions, detailed learning activities and solutions. The book covers: - General management, including innovation, ethics, and sustainability;- Strategic management, including business models, SWOT analyses and internationalisation;- Human resource management, including motivating employees, conflict management and work-life balance;- Marketing, including managing service quality, branding and new service development;- Financial management, including budgeting, risk management and forecasting;- Operations management, including food and beverage delivery, revenue management and health and safety. A useful and engaging read for students of tourism, hospitality and events, this book is also a valuable compilation of examples of practice for people working in industry."--
Contributors -- Preface -- Foreword / Jay Kandampully -- Acknowledgements -- Case study 1: Discovering southern Latium: a daily excursion from Rome / Andrea Salustri -- Case study 2: Developing virtual tourism in the wake of COVID-19: a critical function of tourism destination management organizations / Delly M. Chatibura and Nametsegang Motshegwa -- Case study 3: Why workers are not returning to the hospitality and tourism industry: a turning point / Abhijeet R. Shirsat and Jamie Hoffman -- Case study 4: Last time they were here, this time they were not: environmental factors behind the introduction or discontinuation of robot hotels / Binh Nghiêm-Phú and Hǎ̀ng Thị Bích Trần -- Case study 5: The tourism pursuit app - can tourism destinations be gamified? / Ranjana Tiwari -- Case study 6: The role of locational factors in influencing the overall rating experience of hotel visitors: an application of Tripadvisor data in Barcelona / Sushant M. Desale, Andres Artul-Tur and Maria Isabel Osorio-Caballero -- Case study 7: Convert 'good' to 'excellent' tourism governance: improve indigenous engagement / Joo-Ee Gan -- Case study 8: COVID-19: a disaster for heritage business models - Victoria & Albert Museum Case study / Colin Seymour, Kalliopi Fouseki and Ilias Krystallis -- Case study 9: Disaster management for coastal tourism destinations of Odisha / Shwetasaibal Samanta Sahoo and Sarat Kumar Lenka -- Case study 10: Start from scratch: managing the life cycle and sustaining tourist destinations / Senthilkumaran Piramanayagam, Saurabh Kumar Dixit and Alan Vijay -- Case study 11: Water management in hotels using tap specs in conjunction with the Ishikawa approach / Naresh P. Nayak, Julia N. Albrecht and William Coetzee -- Case study 12: Paradise splendour / Snigdharani Mishra, Vasantha Lakshmi and Preeti Narendra -- Case study 13: Café Cherrapunjee: a guest house with a sustainable approach / Kimberley Camelia S. Langstieh and Evarisa Mary Nengnong -- Case study 14: The Twinhill Hotel: revenue management at a family-owned hotel / Rohan Jugran -- Case study 15: To stay or not to stay: how to convince the very first guest of a resort property / Hanik Kader Şanhöz-Özgen -- Case study 16: Mayday, mayday: falling off a legacy / Senthilkumaran Piramanayagam and Saurabh Kumar Dixit -- Case study 17: Learning from Hilton Worldwide - successful corporate social responsibility strategies / Rachel Hyunkyung Lee and Tiffany S. Legendre -- Case study 18: Researching to solve the problem of developing a skilled workforce in tourism and hospitality: a case of the sultanate of Oman / Mohit Kukreti, Amitabh Mishra and Aaarti Dangwal -- Case study 19: Leveraging artificial intelligence in hospitality and tourism for success / Kathryn Hayat -- Case study 20: Solving the drive-through crisis with service blueprinting / Drew Martin and Su Gibson -- Case study 21: Use of customers' satisfaction survey to segment the tourism market / Noelia Sánchez-Casado, José Miguel Navarro-Azorín, María Pilar Jiménez-Medina and Clara Cubillas-Para -- Case study 22: Present your choice of management information system (MIS) mix / Miguel Mayol-Tur and Andres Artal-Tur -- Case study 23: Small events snowballing into large effects - using economic impact analysis with a winter sports non-profit organization / Cass Morgan and Matt Gnagey -- Case study 24: Operations research in tourism: developing tourist circuits / Senthilkumaran Piramanayagam -- Case study 25: Sustainability of artists and craft persons during COVID-19: a Case study of Kalakriti Creations / Kamakshi Maheshwari and Chandradeep Singh -- Case study 26: Sage Bliss: The question of employee equity / Senthilkumaran Piramanayagam and Saurabh Kumar Dixit -- Case study 27: Hotel dream - reinventing the segmentation, targeting and positioning for resilience / M. Selvalakshmi, R.M. Kabila and V.J. Sivakumar. -- Index
Call number adopted from the University of Southern Indiana, David L. Rice Library
Includes bibliographical references and index.
Keywords: Tourism -- Case studies; Hospitality industry -- Case studies; Special events -- Management -- Case studies